2016
DOI: 10.1016/j.actbio.2016.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic induction heating of superparamagnetic nanoparticles during rewarming augments the recovery of hUCM-MSCs cryopreserved by vitrification

Abstract: Cryopreservation by vitrification has been recognized as a promising strategy for long-term banking of living cells. However, the difficulty to generate a fast enough heating rate to minimize devitrification and recrystallization-induced intracellular ice formation during rewarming is one of the major obstacles to successful vitrification. We propose to overcome this hurdle by utilizing magnetic induction heating (MIH) of magnetic nanoparticles to enhance rewarming. In this study, superparamagnetic (SPM) Fe3O4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 72 publications
(62 reference statements)
1
75
0
3
Order By: Relevance
“…For vitrification or low-CPA vitrification, cooling process is very simple compared to programmable slow freezing because the sample is directly immersed in liquid nitrogen for the fastest cooling available (Fahy, 1986b; Fahy et al, 1984; Huang et al, 2015; Wang et al, 2016) (Figure 1D (a)). Because no ice forms in either extra- or intracellular solution, no water or CPA transport across the cell membrane during freezing/thawing occurs (Fahy and Wowk, 2015) (Figure 1D (b).…”
Section: Fundamentals Of Cryopreservationmentioning
confidence: 99%
See 3 more Smart Citations
“…For vitrification or low-CPA vitrification, cooling process is very simple compared to programmable slow freezing because the sample is directly immersed in liquid nitrogen for the fastest cooling available (Fahy, 1986b; Fahy et al, 1984; Huang et al, 2015; Wang et al, 2016) (Figure 1D (a)). Because no ice forms in either extra- or intracellular solution, no water or CPA transport across the cell membrane during freezing/thawing occurs (Fahy and Wowk, 2015) (Figure 1D (b).…”
Section: Fundamentals Of Cryopreservationmentioning
confidence: 99%
“…Its extension form was further successfully used for the design of CPA equilibration for adherent endothelial cells (Davidson et al, 2015). Compared with programmed slow freezing, vitrification/low-CPA vitrification requires comparatively more CPA; therefore CPA addition and removal processes are more time consuming and costly (Choi et al, 2015a; Choi et al, 2015b; Huang et al, 2015; Wang et al, 2016). …”
Section: Fundamentals Of Cryopreservationmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach has been improved for the cryopreservation of organized tissues where even extracellular freezing causes several damages. In fact, in a recent study reported by Wang et al [53], magnetic induction heating of superparamagnetic nanoparticles was successfully applied to enhance rewarming, with promising results of the vitriied human umbilical cord matrix MSC survival.…”
Section: Freezingmentioning
confidence: 99%